The application of mediation (Suhl) in Islamic criminal law - Ab Aziz, Norjihan; Hussin, Nasimah (Universiti Malaya, 2016)
Dispute resolution through mediation or sulh is encouraged in Islam in almost all disputes. Sulh is not only applicable in civil cases such as matrimonial dispute, custody dispute, transaction dispute and inheritance dispute, but could also be applied in criminal cases as well. In the context of Islamic Criminal Law, sulh is applicable in certain criminal offences of hudud, qisas and ta‘zir particularly when involving the right of individuals. Sulh concerning criminal disputes has been exercised during the period of Prophet Muhammad SAW and legalized in the Quran. There are numerous Qur’anic verses and Ahadith that allow sulh to be applied in criminal cases. Pakistan has recently implemented the Islamic criminal law, allowing criminal cases to be resolved through sulh. Therefore, this article aims to examine the concept of sulḥ in criminal cases according to the Quran and Ahadith. This research also analyses how sulh in criminal casesis implemented in Pakistan and to determine whether it complies with the Quran and Ahadith.